2018
DOI: 10.1371/journal.pone.0196287
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of polysaccharides and triterpenoids in Ganoderma lucidum fruit bodies on induction with signal transduction during the fruiting stage

Abstract: Ganoderma lucidum is a medicinal mushroom that has been widely used in East Asia for the treatment of various diseases. The pharmacological activity of this fungus is primarily attributable to the polysaccharides and triterpenoids. In this study, to obtain the fruit bodies with improved content of active constituents, we examined the effect of salicylic acid (SA) and calcium ion on the biosynthesis of polysaccharides and triterpenoids by spraying the chemicals during the fruiting. To explore the underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…pilosula by MeJA elicitation. CpMVK, CpMVD, CpDXS, and CpispS are enzymes belonging to the mevalonate pathway, which is one of the branches of terpenoid biosynthesis [52]. Less obvious changes were found in the expression of the CpMVK, CpDXS , and CpispS genes at 24 h after treatment in the adventitious roots and multiple shoots, which might indicate that these genes did not respond to MeJA, as well as CpAXS and CpRHM involved in the carbohydrate biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…pilosula by MeJA elicitation. CpMVK, CpMVD, CpDXS, and CpispS are enzymes belonging to the mevalonate pathway, which is one of the branches of terpenoid biosynthesis [52]. Less obvious changes were found in the expression of the CpMVK, CpDXS , and CpispS genes at 24 h after treatment in the adventitious roots and multiple shoots, which might indicate that these genes did not respond to MeJA, as well as CpAXS and CpRHM involved in the carbohydrate biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that spraying SA during the fruiting body formation enhanced the accumulation of GAs. SA increased the triterpenoid content by 23.32% compared to the control [32]. In this study, sodium acetate was more effective (28.63%) at inducing the accumulation of GAs in the fruiting body of G. lucidum .…”
Section: Discussionmentioning
confidence: 60%
“…The crude EPS was precipitated by addition of four volumes of absolute ethanol and stored at 4 °C overnight. After centrifugation at 13000 g for 15 min, the precipitate was suspended in 1 M NaOH at 60 °C for 1 h. Phenol-sulfuric acid method was used for the determination of EPS in the supernatant [37].…”
Section: Recombinant Vector Constructionmentioning
confidence: 99%